Optimasi Kualitas Jaringan WIFI Fakultas Melalui Redesain Topologi Dengan Menggunakan Network Simulator 2 - M. Saski; Iwan Iskandar; Novriyanto; Pizaini (STMIK Budi Darma, 2023)
The utilization of WiFi internet networks on campus as tools to support the learning process at the Faculty of Science and Technology is crucial. Therefore, it essential for the campus to provide internet facilities ensure that all activities, including services and the learning process, are effective. This research analyze the quality of WiFi networks at Faculty of Science and Technology using the Quality of Service (QoS) method with parameters such throughput, delay, packet loss, and jitter. In this study, testing was conducted on WiFi networks in three buildings within the Faculty of Science and Technology, under different conditions during peak hours and off-peak hours, using several SSIDs such as Pegawai, Pimpinan, Uinsuska, Labor TIF dan Baru Belajar, with bandwidths of up to 100Mbps. Test results indicate that the values obtained for throughput, delay, packet loss, and jitter in the three buildings were categorized as